Rhizomucor and Scedosporium Infection Post Hematopoietic Stem-Cell Transplant - Dânia Sofia Marques; Carlos Pinho Vaz; Rosa Branca; Fernando Campilho; Catarina Lamelas; Luis Pedro Afonso; Manuel Jacome; Eduardo Breda; Eurico Monteiro; António Campos Júnior (Case Reports in Medicine)
Hematopoietic stem-cell transplant recipients are at increased risk of developing invasive fungal infections. This is a major cause of morbidity and mortality. We report a case of a 17-year-old male patient diagnosed with severe idiopathic acquired aplastic anemia who developed fungal pneumonitis due to Rhizomucor sp. and rhinoencephalitis due to Scedosporium apiospermum 6 and 8 months after undergoing allogeneic hematopoietic stem-cell transplant from an HLA-matched unrelated donor. Discussion highlights risk factors for invasive fungal infections (i.e., mucormycosis and scedosporiosis), its clinical features, and the factors that must be taken into account to successfully treat them (early diagnosis, correction of predisposing factors, aggressive surgical debridement, and antifungal and adjunctive therapies).